Étude sur les besoins en formation clinique et en formation continue des professionnels de la santé des communautés francophones en situation minoritaire - Consortium national de formation en santé (2006)

Communicative sensitivity in the bilingual healthcare setting: A qualitative study of language awareness - Irvine, Fiona. E.; Roberts, Gwerfyl. W.; Jones, Peter; Spencer, Llinos. H.; Baker, Colin. R.; Williams, Cen (Journal of Advanced Nursing, 2006)
Aim. This paper reports on the second phase of a national study in Wales. The research aimed to assess the level of Welsh language awareness amongst healthcare professionals across Wales, and to identify the factors that enhance language choice within service delivery. Background. The literature suggests that language sensitive healthcare practice is central to ensuring high quality care. However, it is evident that language barriers continue to compromise the quality of care within nursing and other health services. One issue that has received little attention is the level of language awareness that healthcare professionals currently demonstrate. Furthermore the factors that influence language choice for bilingual/multilingual speakers are not well explored in the literature. Methods. The study involved semi-structured interviews with a range of healthcare professionals in acute and community settings across Wales. Using a systematic sampling matrix, a purposeful sample of 83 professionals was selected to participate. Twenty-seven of the respondents were nurses, health visitors and midwives. The interviews focussed on the factors that facilitate or impede language sensitive healthcare practice. All interviews were audiotaped and, using a framework analysis approach, conceptual codes were developed and defined and categories and sub-categories were constructed to create thematic charts. Findings. Three main themes were identified: care enhancement, which focussed on the process and outcome of offering language choice to bilingual patients; organizational issues, which reflected issues relating to the infrastructure of service provision; and training implications, which focused on Welsh language learning in health care. Conclusions. Complex dynamics of language use are in operation within bilingual healthcare settings and organizational as well as individual factors are important in facilitating appropriate language use. Many of the issues highlighted are not peculiar to the Welsh context, but apply to healthcare settings across the world, where other minority languages are in use.

Préparer le terrain. Soins de santé primaires en français dans le Sud de l'Ontario. Rapport régional - Réseau franco-santé du Sud de l'Ontario (2006)

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau Santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)